Aumento de fijación de nitrógeno en diazótrofos unicelulares versus Trichodesmium tras un evento de deposición de polvo atmosférico en las Islas Canarias - Benavides, Mar (2012)
En este trabajo hemos estudiado la relación entre la deposición de polvo atmosférico, y la abundancia y tasas de fijación de nitrógeno asociadas a Trichodesmium y fijadores unicelulares en las Islas Canarias. La fijación de nitrógeno asociada a los fijadores unicelulares aumentó entre el 86 y el 92% tras un evento de deposición de polvo atmosférico, mientras que la asociada a Trichodesmium disminuyó entre el 34 y el 92%. Tras el evento de deposición de polvo, aumentó la abundancia de fijadores unicelulares y la mayoría de éstos aparecieron asociados a partículas de materia orgánica. Creemos que esta estrategia les permite ligar el hierro que contiene el polvo y así poder usar este nutriente limitante. We have studied the relationship between atmospheric dust deposition, N2 fixation rates and the abundance of unicellular diazotrophs and Trichodesmium in weekly or fortnightly samplings over three months in the Canary Islands. On average, N2 fixation rates by unicellular diazotrophs and Trichodesmium were low (0.2 and 1.66 x 10-3 nmol N L-1 h-1, respectively). However, N2 fixation rates associated with unicellular diazotrophs increased by 86 and 92% after a peak of aerosol concentrations in samples incubated in both light and darkness, while the rates associated with Trichodesmium diminished by 34 and 92% in the light and in the dark, respectively. The abundance of unicellular diazotrophs ranged from 3.98 to 53.97 cell L-1. After the input of aerosols, 66% of the unicellular diazotrophs observed appeared attached to putatively organic matter particles. We hypothesize that this strategy confers them the ability to better trap and process dust particles through binding of iron (Fe) with organic molecules. On the contrary, the abundance of Trichodesmium was low (average of 0.54 trichomes L-1), which appeared majorly in the form of free trichomes. Being present as free trichomes instead of colonies might hinder the ability of these organisms to take advantage of the Fe dissolved in the water column after dust ...